Technology Integration in Mathematics Education: Examining the Quality of Meta-Analytic Research - Young, Jamaal Rashad (International Journal on Emerging Mathematics Education, 2017)
The aim of this study was to evaluate the methodological quality of meta-analyses in mathematics education research. Computerized searches were conducted in ERIC, PsycINFO, ProQuest, and JSTOR through January 2016 for meta-analyses pertinent to technology integration in the mathematics classroom.Â  To identify studies, mathematics subject matter terms such as âsystematic reviewâ, literature reviewâ and âmeta-analysisâ were used. Retrieved studies were screened, extracted, and the methodological quality was evaluated using the 11-item Revised Assessment of Multiple Systematic Reviews (R-AMSTAR). The characteristics of meta-analyses associated with the methodological reporting quality were identified. Results suggest that on average the quality of methodological reporting is good, but there are several areas of concern. Implications are provided to improve research and classroom practice in this area.